Effects of Quartz Powder as a Partial Replacement of Cement on Fresh and Hardened Properties of Normal and High Strength Concretes - Ahmadi, Ali Asghar Ashrafi Soltan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Concrete is the most extensively material used in civil engineering applications all over the world, and cement is the most essential constituent of concrete. The production of cement is responsible for about 8% of greenhouse gases emission into the air that assists the global warming. Consequently, in recent years, there has been an increased interest in the use of waste pozzolanic admixtures to supplement cement. Replacing cement with these admixtures has been known to reduce the cost of producing concrete, the air pollution resulting from cement production, as well as enhance certain concrete properties. The relatively low cost, high availability, and high silica content in quartz powder has made it more popular compared to other waste natural pozzolans. As such, a significant amount of research is increasingly being directed towards evaluating the effects of quartz powder in cement. When used to partially replace cement in concrete, quartz powder acts as filler for the spaces in the cement paste. Due to the „very fine‟ nature of its particles (less than 1 μm in size), quartz powder increases the density and homogeneity of the cement paste, thereby enhancing the concrete‟s compressive strength and its overall quality in both its fresh and hardened states. This study, evaluates the effects of five different percentages of quartz powders as a partial replacement of cement namely 0, 10, 20, 30 and 40% on the mechanical and physical properties of concrete of three classes of concrete namely C20/25, C35/45, and C50/60. For this aim, workability (assisted by slump test) test, compressive and flexural strength tests, permeability by the rapid chloride test, water absorption capacity test, and heat resistance test were done. Finally, comparison is done between the results of control concrete and quartz powder test specimens. The test results shows that using 10% of quartz powder (QP) as a partial replacement of cement has a significant effect on the physical and mechanical properties of concrete such as a workability, compressive strength, flexural strength, resistance to chloride penetration and water absorption capacity for different classes of concretes (C20/25, C35/45 and C50/60).

ÖZ: Beton dünyada inşaat mühendisliği uygulamalarında kullanılan en yaygın malzeme olmakla birlikte, çimento betonun en temel bileşenidir. Çimento üretimi, küresel ısınmaya sebep olan sera gazı emisyonunun yaklaşık 8%‟inden sorumludur. Sonuç olarak, son yıllarda atık pozolonik katkılarının çimentonun içine takviye edilmesi konusunda artan bir ilgi vardır. Çimentoya bu katkı malzemelerinin katılması, beton üretim maliyetlerini düşürdüğü, çimento üretiminden kaynaklanan hava kirliliğinin yanı sıra belirli özelliklerini de arttırdığı bilinmektedir. Nispeten düşük maliyetli yüksek erişilebilirlik ve kuvars tozundaki yüksek silika içeriği diğer atık doğal pozolanlara kıyasla bunu daha popüler hale getirdi. Bu nedenle, çimentoda kuvars tozunun etkilerini değerlendirmeye yönelik hızla önemli araştırmalara yönlenilmektedir. Betonda çimentoyu kısmen değiştirirken kuvars tozu çimento macunundaki boşluklar için dolgu maddesi görevi görür. Parçacıkların “ çok ine” doğası nedeni ile (1μm‟den küçük boyutta), kuvars tozu çimento macununun yoğunluğunu ve homojenliğini artırır. Böylece hem taze hem de sertleşmiş haldeki betonun basınç direncini ve genel kalitesini artırır. Bu çalışma, beş farklı yüzdelik (0%, 10%, 20%, 30% ve 40%) ile kısmi kuvars tozunun değiştirilmesinin üç farklı sınıftaki betonun (C20/25, C35/45 ve C50/60) mekanik ve fiziksel özellikleri üzerindeki etkilerini göstermektedir. Bunun amacı, işlenebilirlik ( çökme testine yardımcı olarak ) testi, bacınç ve eğilme testi, hızlı klorür ile geçirgenlik testi, su emme kapasite testi ve ısı direnci testlerinin yapılmış olması. Sonuç olarak, beton kontrolünün sonuçları ve kuvars tozunun numuneleri arasındaki kıyaslama bitmiş bulunmaktadır. Test sonuçları gösteriyor ki; 10% kuvars tozu (QP) kullanılarak kısmi değişiklik yapılmış çimento, betonun mekanik ve fiziksel özelliklerinde; işlenebilirlik, basınç direnci, bükülme direnci, klorür penetrasyonuna direnç ve su emilim kapasitesi üç farklı sınıf betona (C20/25, C35/45, C50/60) önemli etki yapmıştır .
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2018. Supervisor: Assoc. Prof. Dr. Khaled Hamed Marar.
Keywords: Civil Engineering; Construction Materials; Building Materials--Cement; Compressive Strength; Flexural Strength; Heat Resistance; Rapid Chloride Permeability; Quartz Powder; Splitting Tensile Strength; Workability